Schiff Bases: Multipurpose Pharmacophores with Extensive Biological Applications - Khurram Shahzad Munawar,; Shah Muhammad Haroon,; Syed Ammar Hussain ,; Hamid Raza, (Journal of Basic & Applied Sciences, 2018)
Schiff bases are substances prepared generally by the condensation reaction of aldehydes or ketones with amines. They may have substituted aliphatic or aromatic side chains, and hence show extensive biological activities. It is reported that these molecules play an important role in the synthesis of various drugs. This paper focus on the biological activities of Schiff bases of various types and hence makes them important precursors in designing drugs for medical treatment. The biological applications of Schiff bases can be extended from antimicrobial, plant growth regulator, antioxidant, enzymatic, anticancer, anti-inflammatory, anti-malarial, antiviral, neuroprotective, analgesic, anti-convulsant to neurotoxic activities. They also serve as a dominant class of ligands with a variety of binding sites for coordination with metals.